Kepuasan Masyarakat terhadap Pelayanan Dinas Perhubungan Kabupaten Takalar - Rahmatiah, Andi; Rani, Andi Patta; Rifai, Nur Ilmiah (Jurnal Publisitas, 2022)
This study aims to measure people's satisfaction with the services of the Department of Transportation, Takalar Regency based on street light services, and terminal services. This study uses a quantitative method with a non-probability sampling technique, with a Likert scale measurement involving 100 respondents, namely: Entrepreneurs, Housewives, Farmers, Students, Private Employees, Retirees, BUMN/BUMD Employees, Civil Servants. Determination of the sample is done by purposive sampling. The results showed that the service of the Department of Transportation, Takalar Regency was in the poor category of 71.83%, with service quality C. Street light service was higher at 72.04% compared to terminal services which was only 69.44%. The highest street light service element is in the cost/tariff section with a value of 3.80 and the lowest is on the elements of handling, complaints, suggestions and input services with a value of 2.46. While the terminal services for handling, complaints, suggestions and inputs received the lowest score, namely 1.00, while for other service elements each with a value of 3.00.